The role of land use in terrestrial support of boreal lake food webs - Ossi Keva; Matthew R. D. Cobain; Antti P. Eloranta; Heikki Hämäläinen; Mikko Kiljunen; Jos Schilder; Roger I. Jones (Nature Communications)
Abstract There is growing awareness of the importance of cross-boundary energy and nutrient transfers between adjacent ecosystems. Lake ecosystems receive inputs of terrestrial organic matter that microbes can make available to higher level consumers. However, how environmental drivers influence this terrestrial support of benthic and pelagic consumers at multiple trophic levels remains underexplored. Using hydrogen stable isotopes as a tracer of terrestrial organic matter, we find large variation in terrestrial support of aquatic consumers (i.e., consumer allochthony) among 35 boreal lakes. Of 19 different aquatic organisms, benthic consumers show the highest allochthony. Consumer allochthony decreases along an environmental gradient from forested to agricultural catchments, likely due to shifts in the origin and nature of lake organic matter. Our results demonstrate how cross-ecosystem transfer of organic matter can influence community dynamics in recipient ecosystems, with anthropogenic management of donor terrestrial ecosystems affecting the structure and function of food webs in recipient aquatic ecosystems.